2012
DOI: 10.1155/2012/929025
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Injection for Hypertensive Renal Damage: A Systematic Review

Abstract: Objective. To evaluate the effectiveness of astragalus injection (a traditional Chinese patent medicine) for patients with renal damage induced by hypertension according to the available evidence. Methods. We searched MEDLINE, China National Knowledge Infrastructure (CNKI), Chinese VIP Information, China Biology Medicine (CBM), and Chinese Medical Citation Index (CMCI), and the date of search starts from the first of database to August 2011. No language restriction was applied. We included randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Thirdly, the primary goal of treatment for EH is to reduce the mortality or prevent progression to severe complications [64]. Only one trial [26] reported the 5-year follow-up of Tai Chi.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the primary goal of treatment for EH is to reduce the mortality or prevent progression to severe complications [64]. Only one trial [26] reported the 5-year follow-up of Tai Chi.…”
Section: Discussionmentioning
confidence: 99%
“…An important reason is that achievements in herbal pharmacology cannot be effectively converted to appropriate clinical use. It is thought that syndrome differentiation, the traditional therapy, has perfect effects in improving the signs, symptoms, and syndrome in TCM, but poor effects in treating disease (and even no effects in improving the key indicators of diseases) [84]. Therefore, application of the achievements of herbal pharmacology in clinical treatment is an important reference for lowering BP using Chinese herbs and formulas.…”
Section: Application Of Herbal Pharmacological Achievements In CLImentioning
confidence: 99%
“…Multicenter randomized controlled clinical trials have shown that CHM therapy improves estimated glomerular filtration rate (eGFR) in both patients with stage 3chronic kidney disease (CKD) and idiopathic membranous nephropathy [ 13 , 14 ]. Many CHM preparations have been used in treating CKD in China, and systematic reviews have shown that some are effective [ 15 , 16 ]. Investigations on CHM treatment of DKD have been undertaken in China.…”
Section: Introductionmentioning
confidence: 99%